Attributing non-specific symptoms to cancer in general practice: A scoping review. - Gladys Langue; India Pinker; Valerie Moran; Sophie Pilleron (PLoS ONE, 2025)
Background Non-specific cancer symptoms are challenging to interpret in general practice. They can be attributed to a wide range of other conditions and delay the cancer diagnosis, increasing the risk of poor outcomes. Aim To summarise existing knowledge on the attribution of non-specific symptoms to potential cancer in general practice and identify gaps in the literature. Method We conducted a scoping review, following Joanna Briggs Institute's guidance and reported according to the PRISMA for scoping reviews checklist. Non-specific symptoms were defined based on NICE guidelines for suspected cancer. We systematically searched six databases and search engines for original papers, systematic reviews and doctoral theses. Two reviewers independently screened titles, abstracts, full-texts and reference lists. Included articles were then uploaded to the AI-based tool ResearchRabbit to identify further papers. Findings were synthesised using the Refined Andersen Model of Total Patient Delay. Results Eight studies were included. These addressed fatigue, recurrent infection, pallor, weight loss, and deep vein thrombosis, with general practitioners (GPs) defining the latter two as cancer-specific. Factors influencing attribution to cancer included pre-existing conditions, the number, type and combination of symptoms as well as GPs' gut feeling and knowledge, patients' concern, and the frequency of medical visits. Conclusion This scoping review identified a limited number of studies on the attribution of non-specific symptoms to potential cancer in general practice, with symptoms such as pruritus and new-onset diabetes not addressed. It highlights the need for further research into GPs diagnostic reasoning related to non-specific cancer symptoms, especially on under-researched symptoms.